Rodzina wiejska jako środowisko kształtowania aspiracji dzieci i młodzieży - Palka, Katarzyna (Karkonoska Państwowa Szkoła Wyższa, 2011)
Parents have asignificant impact on childreris decision about choice of their path of life. For years, forming of the level of parents and their children's educational and occupational spirations was affected by living conditions of families from rural areas, difficult financial situation and worse education conditions of village schools. The aim of the research was presenting the mechanism of forming the educational and occupational aspirations of secondary school (Polish: gimnazjum) pupils in the country and in town and defining the relations between background conditions (including family background) and the level of pupils' educational and occupational aspirations. Particularly, the answer the question was tried to find - what are conditions of pupils of village secondary schools' life's aspirations (educational and occupational)? Presented results of the research are only the fragment of wider survey of conditions of young people's aspirations. Among numerous conditions, which have been analysed, the factors of family background appeared, such as: number of family members, families' financial and materiał conditions, parents' education, parents' aspirations to their children's education and family traditions connecting with working in particularprofession.
Keywords: wieś; rodzina; dzieci; młodzież; edukacja